RF/microwave circuit design for wireless applications - Rohde, Ulrich L.; Rudolph, Matthias (Wiley / John Wiley & Sons, 2013)
Provides researchers and engineers with a complete set of modeling, design, and implementation tools for tackling the newest IC technologiesRevised and completely updated, RF/Microwave Circuit Design for Wireless Applications, Second Edition is a unique, state-of-the-art guide to wireless integrated circuit design that provides researchers and engineers with a complete set of modeling, design, and implementation tools for tackling even the newest IC technologies. It emphasizes practical design solutions for high-performance devices and circuitry, incorporating ample examples of novel and clever circuits from high-profile companies.Complete with excellent appendices containing working models and CAD-based applications, this powerful one-stop resource:Covers the entire area of circuit design for wireless applicationsDiscusses the complete system for which circuits are designed as well as the device technologies on which the devices and circuits are basedPresents theory as well as practical issuesIntroduces wireless systems and modulation typesTakes a systematic approach that differentiates between designing for battery-operated devices and base-station designRF/Microwave Circuit Design for Wireless Applications, Second Edition is an indispensable tool for circuit designers; engineers who design wireless communications systems; and researchers in semiconductor technologies, telecommunications, and wireless transmission systems